2007
DOI: 10.1038/nature05673
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 controls regulatory T-cell function by interacting with AML1/Runx1

Abstract: Naturally arising CD25+CD4+ regulatory T cells (T(R) cells) are engaged in the maintenance of immunological self-tolerance and immune homeostasis by suppressing aberrant or excessive immune responses, such as autoimmune disease and allergy. T(R) cells specifically express the transcription factor Foxp3, a key regulator of T(R)-cell development and function. Ectopic expression of Foxp3 in conventional T cells is indeed sufficient to confer suppressive activity, repress the production of cytokines such as interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
549
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 608 publications
(578 citation statements)
references
References 28 publications
25
549
1
3
Order By: Relevance
“…First, DM inhibited known targets of BMP signalling including SMAD1/5/ 8. Second, DM suppressed the transcription of IL2, a RUNX1-target gene [15]. Consistently, we have found that BMP signalling increased the level of phorsphorylation of RUNX1 protein, while DM decreased it.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…First, DM inhibited known targets of BMP signalling including SMAD1/5/ 8. Second, DM suppressed the transcription of IL2, a RUNX1-target gene [15]. Consistently, we have found that BMP signalling increased the level of phorsphorylation of RUNX1 protein, while DM decreased it.…”
Section: Discussionsupporting
confidence: 84%
“…6). We previously reported that RUNX1 was involved in IL-2 transcription, and that knockdown of RUNX1 completely suppressed IL-2 production in Jurkat cells [15]. Thus, it is interesting that the suppression of IL-2 by DM is coupled with the decrease of the phosphorylated form of RUNX1.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations